Stage-specific sensitivity of fecal immunochemical tests for detecting colorectal cancer: systematic review and meta-analysis - Niedermaier, Tobias; Balavarca, Yesilda; Brenner, Hermann (The American journal of gastroenterology, 2019)
OBJECTIVE: Fecal immunochemical tests (FITs) detect the majority of colorectal cancers (CRCs), but evidence for variation in sensitivity according to the CRC stage is sparse and has not yet been systematically synthesized. Thus, our objective was to systematically review and summarize evidence on the stage-specific sensitivity of FITs. METHODS: We screened PubMed, Web of Science, Embase, and the Cochrane Library from inception to June 14, 2019, for English-language articles reporting on the stage-specific sensitivity of FIT for CRC detection using colonoscopy as a reference standard. Studies reporting stage-specific sensitivities and the specificity of FIT for CRC detection were included. Summary estimates of sensitivity according to the CRC stage and study setting (screening cohorts, symptomatic/diagnostic cohorts, and case-control studies) were derived from bivariate meta-analysis. RESULTS: Forty-four studies (92,447 participants including 3,034 CRC cases) were included. Pooled stage-specific sensitivities were overall very similar but suffered from high levels of imprecision because of small case numbers when calculated separately for screening cohorts, symptomatic/diagnostic cohorts, and case-control studies. Pooled sensitivities (95% confidence intervals) for all studies combined were 73% (65%-79%) for stage-I-CRCs and 80% (74%-84%), 82% (77%-87%), and 79% (70%-86%) for the detection of CRC stages II, III, and IV, respectively. Even substantially larger variation was seen in sensitivity by T-stage, with summary estimates ranging from 40% (21%-64%) for T1 to 83% (68%-91%) for T3-CRC. DISCUSSION: Although FITs detect 4 of 5 CRCs at stages II-IV, the substantially lower sensitivity for stage-I-CRC and, in particular, T1 CRC indicates both need and potential for further improvement in performance for the early detection of CRC.
Gesehen am 24.06.2020